Innovation and human resources practices in companies of Southern Brazil - Serafin, Vanessa Faedo; Severo, Eliana Andréa; De Guimarães, Julio Cesar Ferro; Rotta, Claudio; Philereno, Deivis Cassiano (Revista de Administração da UFSM, 2022)
Purpose: The purpose of the study is to analyze the relationships between process innovation, human resources practices and the competitive advantage of organizations, through seven research hypotheses. Design/methodology/approach: The methodology used is a descriptive, quantitative study applied to 207 human resources professionals from companies in the south of Brazil, analyzed by the modeling of structural equations. Findings: The hypotheses predicted that process innovation and human resources practices would be positively related to competitive advantage, as well as process innovation would be positively correlated with human resources practices. The results confirmed the direct relationships supported by the hypotheses. Practical implications: Regarding the managerial contributions, the present study brought important information to direct the strategic actions of the companies, integrating process innovation and human resources practices to generate competitive advantage, having human resources management as an important vector for the company strategy, guiding individuals towards the companies’ objectives. Originality/value: The originality of the study consists in the construction of a theoretical framework on the relationships between process innovation, human resources practices and the competitive advantage of organizations, which can be used by other researches and thus advance in the Theory of Administration.